Clinicopathological characteristics of 4 cases of spiradenoma - Jingmei ZHENG; Huan CHEN; Fuhan ZHANG; Yingying GUAN; Qiuli JIANG; Huadong LU; Jianfang XU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To investigate clinical pathological characteristics and pathological diagnosis, to provide help for spiradenoma (SA). Methods Clinical data and pathological features of 4 patients with SA in our hospital were analyzed retrospectively, and clinical and pathological features were summarized with the review of literatures. Results The average age of 4 patients with SA was (34.00±6.83) years old. 2 cases occurred in the back and 2 cases in the left upper arm. The course of disease was 1-10 years. All 4 cases were benign cutaneous spiral Adenoma, which were composed of two kinds of cells. Immunohistochemistry showed that epithelial and myoepithelial differentiation, a small amount of p53 was positive, Ki-67 index was about 5% positive. 4 cases of SA were followed up from 16 months to 39 months, and there were no signs of recurrence or malignant transformation. Conclusion SA occurs subcutaneously and needs to be diagnosed by histopathology. Its biological behavior is benign and its prognosis is good.